LED Lighting in Horticulture - Kaur, Jagmeet (My University, 2018)
LED based lighting is designed by using Mathematical Equations in numerical Programming, consisting two different coloured LEDs, i.e., red and blue. Using the theoretical results we designed the actual panel in which the LEDs are arranged in such a way that the plants placed under the LED panel can get uniform illumination. It is an improved version as it can provide stage specific lighting and crop specific lighting i.e. the intensity of light can be altered accordingly.
Master of Science- Physics
Keywords: Led Lighting; Horticulture; stage specific